Carbohydrate Quality Metrics and Their Association with Population Nutrient Intakes and Diet Quality in Australia. (29th May 2020) - Blumfield, Michelle; McConnell, Andrew; Campos, Vanessa; Lê, Kim-Anne; Fayet-Moore, Flavia
Abstract: Objectives: Carbohydrate (CHO) quality is important for health, yet it is unclear how to best define CHO quality. The aim of this study was to investigate whether diets that meet one of three CHO quality ratios, that include a combination of grams of CHO, fiber or free sugars, are associated with improved diet quality in Australia. Methods: National data from the 2011–12 Australian National Nutrition and Physical Activity Survey were assessed (n = 12, 153; age 49.0 ± 16.4y adults, 9.5 ± 5.0y children). Three CHO quality ratios were defined: (i) Simple ratio, 10:1 (10 g CHO: ³1 g fiber); (ii) Modified ratio, 10:1:2 (10 g CHO: ³1 g fiber: £2 g free sugars); and (iii) Dual ratio, 10:1 & 1:2 (10 g CHO: ³1 g fiber & £2 g free sugars per 1 g fiber). Participants were defined as having met or not met each ratio in terms of total daily nutrient intakes. Dietary data were collected using a validated Automated Multiple-Pass Method. Nutrient intakes and food group data were compared to Australian Nutrient Reference Values and an Australian Healthy Eating Index (HEIFA-2013). Results: Prevalence of ratio adherence was: simple ratio (45%), modified ratio (30%) and dual ratio (36%). After adjusting for energy intake, adults and children who met a ratio reported lower energy intakes, higher fiber and micronutrient intakes, higher HEIFA-2013 scores (adults only) and lower intakes of total sugars, added sugars and sodium ( P < .001 for all), compared to those who failed to meet any ratio. Compared to the simple ratio, modified and dual ratios further decreased adult intakes of total sugars (95 g modified, 71 g dual vs 116 g simple; P < .001), added sugars (36 g, 16 g vs 57 g; P < .001) and free sugars (50 g, 26 g vs 72 g; P < .001), and increased HEIFA-2013 scores (56, 59 vs 51; P < .001), with similar findings in children. Conclusions: All three CHO quality metrics identified diets with higher nutrient intakes and HEIFA-2013 scores, with the addition of a free sugars constraint resulting in further improvements in diet quality. Utility of a CHO quality metric, based on CHO, fiber and free sugars, may offer a simple, standardized approach to improve total diet quality, which has potential for high public health impact. Funding Sources: Nestlé Research.